2019
DOI: 10.1111/ene.13971
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of neuroinflammation in patients after mild traumatic brain injury: a longitudinal 123I‐CLINDE single photon emission computed tomography study

Abstract: Background and purpose Neuroinflammation has been proposed as part of the pathogenesis of post‐concussion symptoms (PCS), but the inflammatory response of the human brain to mild traumatic brain injury (mTBI) remains unknown. We hypothesized that a neuroinflammatory response is present in mTBI at 1–2 weeks post‐injury and persists in patients with PCS. Methods We scanned 14 patients with mTBI without signs of structural damage at 1–2 weeks and 3–4 months post‐injury and 22 healthy controls once using the singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 24 publications
0
32
0
1
Order By: Relevance
“…There is limited clinical research on glial activation following mTBI; however, the emergence of positron emission tomography (PET) tracers that bind to the 18 kDa translocator protein (TSPO) that is associated with microglia has enabled in vivo clinical imaging of microglial activation. Eber et al found that at 1-2 weeks and 3-4 months post-mTBI, patients who had sustained an mTBI had significantly higher TSPO binding when compared to healthy controls [77]. Additionally, a preliminary study of former athletes with an extensive history of mTBI found significantly higher TSPO expression in comparison to healthy age-matched controls [78].…”
Section: Mild Tbimentioning
confidence: 99%
“…There is limited clinical research on glial activation following mTBI; however, the emergence of positron emission tomography (PET) tracers that bind to the 18 kDa translocator protein (TSPO) that is associated with microglia has enabled in vivo clinical imaging of microglial activation. Eber et al found that at 1-2 weeks and 3-4 months post-mTBI, patients who had sustained an mTBI had significantly higher TSPO binding when compared to healthy controls [77]. Additionally, a preliminary study of former athletes with an extensive history of mTBI found significantly higher TSPO expression in comparison to healthy age-matched controls [78].…”
Section: Mild Tbimentioning
confidence: 99%
“…In addition, symptoms commonly observed following SRC have also been reported in a variety of other conditions such as polytrauma, infection, and mental illness [2][3][4][5]. In views of this, inflammation presents as a unifying concept, as it has not only been associated with concussion-like symptoms across numerous medical conditions [5], but is increasingly recognized as an important and prominent feature of concussion secondary injury [6][7][8][9][10]. Therefore, investigating the relationship between inflammation and symptom burden following concussion may help elucidate clinically meaningful pathophysiological mechanisms that mediate patient recovery [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, rodent studies have repeatedly demonstrated an inflammatory response following mTBI with acute and delayed activation of microglia and astrocytes and an increased cytokine production both systemically and within the brain 14 . Recently, the first study in humans using molecular imaging demonstrated neuroinflammation after mTBI was published, with findings indicating neuroinflammation of deeper brain regions 3‐4 months after mTBI, and with correlation to presence of post‐concussion symptoms 15 …”
Section: Discussionmentioning
confidence: 99%